ANALISIS TENTANG MANFAAT KEIKUTSERTAAN MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN DALAM ORGANISASI KEMAHASISWAAN SE-LINGKUNGAN FKIP UNIVERSITAS RIAU - Wahyu, M. Hasyir; Erlinda, Sri; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the influence of student organizations in shaping the character of students as potential carriers of change. So that student organizations are considered as the right place to hone soft skills and hard skills of students in order to prepare supplies for the future. Therefore, the authors take the research title